A CASE SERIES ON ANTI NMDAR ENCEPHALITIS - Reji, Reshma; Alexander, Sherin; Vijayan, Meenu (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune neurological disorder arising from the generation of antibodies which binds to the synaptic proteins. Here we present a case series of 3 cases where the different aspects of treating NMDAR encephalitis are dealt with. The association of ovarian teratoma and the importance of its removal before treating the encephalitis have been discussed in the second case. Apart from the first line and second line agents used in the therapy of NMDAR encephalitis, the importance of managing infections especially urinary tract infection and lower respiratory tract infection with antibiotics have also been discussed. The article also aims to throw light into the treatment of extrapyramidal side effects induced by antipsychotics. At the end, the significance of putting the patient on a ketogenic diet to manage refractory seizures associated with anti-NMDA receptor encephalitis has also been discussed based on reviewing literature.